Using self- and peer-assessments for summative purposes: analysing the relative validity of the AASL (Authentic Assessment for Sustainable Learning) model. Issue 6 (17th August 2016) - Kearney, Sean; Perkins, Timothy; Kennedy-Clark, Shannon
Abstract : The purpose of this paper is to provide a proof of concept of a collaborative peer-, self- and lecturer assessment processes. The research presented here is part of an ongoing study on self- and peer assessments in higher education. The authentic assessment for sustainable learning (AASL) model is evaluated in terms of the correlations between sets of marks. The article provides an explanation of the assessment process, and analyses sets of marks as a means of justifying the validity of the process. The results suggest that students, even those with no prior experience in peer- or self-evaluation, in their first year of tertiary study, under the right conditions, are able to accurately judge their own work and make reasonably accurate judgements of the work of their peers. While previous studies have expounded the benefits of self- and peer assessments in tertiary study, undertaking a prescribed process, such as AASL, has a further implication in allowing others to replicate the process with reasonable assuredness of the validity of the process across various fields of study.